Demo abstract: Integrating a driving simulator with city-scale VANET simulation for the development of next generation ADAS systems - Buse, Dominik S.; Sommer, Christoph; Dressler, Falko (IEEE INFOCOM 2018 - IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

Guest Editorial: Introduction to the Special Issue on Advances in Smart and Green Transportation for Smart Cities - Djahel, Soufiene; Sommer, Christoph; Marconi, Annapaola (IEEE Transactions on Intelligent Transportation Systems)

Readjusting the privacy goals in Vehicular Ad-Hoc Networks: A safety-preserving solution using non-overlapping time-slotted pseudonym pools - Eckhoff, David; Sommer, Christoph (Computer Communications)

Cooperative vehicle applications with cellular communication - Gläser, Stefan; Sommer, Christoph; Gehlen, Guido; Sories, Sabine (ATZelektronik worldwide)

Vehicular micro cloud in action: On gateway selection and gateway handovers - Hagenauer, Florian; Sommer, Christoph; Higuchi, Takamasa; Altintas, Onur; Dressler, Falko (Ad Hoc Networks)

A simulative analysis of the performance of IEEE 802.11p and ARIB STD-T109 - Heinovski, Julian; Klingler, Florian; Dressler, Falko; Sommer, Christoph (Computer Communications)

The Impact of Head of Line Blocking in Highly Dynamic WLANs - Klingler, Florian; Dressler, Falko; Sommer, Christoph (IEEE Transactions on Vehicular Technology)

Bloom Hopping: Bloom Filter Based 2-Hop Neighbor Management in VANETs - Klingler, Florian; Cohen, Reuven; Sommer, Christoph; Dressler, Falko (IEEE Transactions on Mobile Computing)

Backwards compatible extension of CAMs/DENMs for improved bike safety on the road - Loewen, Stefan; Klingler, Florian; Sommer, Christoph; Dressler, Falko (2017 IEEE Vehicular Networking Conference (VNC))

On the need for coordinated access control for vehicular visible light communication - Memedi, Agon; Sommer, Christoph; Dressler, Falko (2018 14th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

Investigation of the impact of a wireless Fog Warning System with respect to road traffic on a highway - Outay, Fatma; Ahmar, Absar-Ul-Haque; Kamoun, Faouzi; Yasar, Ansar-Ul-Haque; Sommer, Christoph; Jabeur, Nafaa; El-Amine, Samar (Personal and Ubiquitous Computing)

QQDCA: Adapting IEEE 802.11 EDCA for unicast transmissions at high topology dynamics - Pannu, Gurjashan Singh; Klingler, Florian; Sommer, Christoph; Dressler, Falko (2017 IEEE Vehicular Networking Conference (VNC))

Duplicate suppression for efficient floating car data collection in heterogeneous LTE-DSRC vehicular networks - Turcanu, Ion; Klingler, Florian; Sommer, Christoph; Baiocchi, Andrea; Dressler, Falko (Computer Communications)

Performance Assessment of IEEE 802.11p with an Open Source SDR-Based Prototype - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (IEEE Transactions on Mobile Computing)

On the impact of antenna patterns on VANET simulation - Eckhoff, David; Brummer, Alexander; Sommer, Christoph (2016 IEEE Vehicular Networking Conference (VNC))

Marrying safety with privacy: A holistic solution for location privacy in VANETs - Eckhoff, David; Sommer, Christoph (2016 IEEE Vehicular Networking Conference (VNC))

Poster: Using clusters of parked cars as virtual vehicular network infrastructure - Hagenauer, Florian; Sommer, Christoph; Higuchi, Takamasa; Altintas, Onur; Dressler, Falko (2016 IEEE Vehicular Networking Conference (VNC))

Parked Cars as Virtual Network Infrastructure - Hagenauer, Florian; Sommer, Christoph; Higuchi, Takamasa; Altintas, Onur; Dressler, Falko (Proceedings of the 2nd ACM International Workshop on Smart, Autonomous, and Connected Vehicular Systems and Services - CarSys '17)

Vehicular Micro Clouds as Virtual Edge Servers for Efficient Data Collection - Hagenauer, Florian; Sommer, Christoph; Higuchi, Takamasa; Altintas, Onur; Dressler, Falko (Proceedings of the 2nd ACM International Workshop on Smart, Autonomous, and Connected Vehicular Systems and Services - CarSys '17)

Simulating a city-scale community network: From models to first improvements for Freifunk - Hardes, Tobias; Dressler, Falko; Sommer, Christoph (2017 International Conference on Networked Systems (NetSys))

Performance comparison of IEEE 802.11p and ARIB STD-T109 - Heinovski, Julian; Klingler, Florian; Dressler, Falko; Sommer, Christoph (2016 IEEE Vehicular Networking Conference (VNC))

Poster - Klingler, Florian; Pannu, Gurjashan Singh; Sommer, Christoph; Dressler, Falko (Proceedings of the 23rd Annual International Conference on Mobile Computing and Networking - MobiCom '17)

Poster - Klingler, Florian; Pannu, Gurjashan Singh; Sommer, Christoph; Bloessl, Bastian; Dressler, Falko (Proceedings of the 15th Annual International Conference on Mobile Systems, Applications, and Services - MobiSys '17)

Pick the right guy: CQI-based LTE forwarder selection in VANETs - Turcanu, Ion; Sommer, Christoph; Baiocchi, Andrea; Dressler, Falko (2016 IEEE Vehicular Networking Conference (VNC))

Protocol options for low power sensor network MAC using wake-up receivers with duty cycling - Blobel, Johannes; Sommer, Christoph; Dressler, Falko (2016 IEEE International Conference on Communications (ICC))

On the impact of adjacent channel interference in multi-channel VANETs - Campolo, Claudia; Sommer, Christoph; Dressler, Falko; Molinaro, Antonella (2016 IEEE International Conference on Communications (ICC))

Special Issue on Multi-radio, Multi-technology, Multi-system Vehicular Communications - Campolo, Claudia; Cheng, Lin; Sommer, Christoph; (Michael) Tsai, Hsin-Mu (Computer Communications)

Cars as the base for service discovery and provision in highly dynamic networks - Hagenauer, Florian; Sommer, Christoph; Merschjohann, Simon; Higuchi, Takamasa; Dressler, Falko; Altintas, Onur (2016 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

Interconnecting smart cities by vehicles: How feasible is it? - Hagenauer, Florian; Sommer, Christoph; Onishi, Ryokichi; Wilhelm, Matthias; Dressler, Falko; Altintas, Onur (2016 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

Cars as a main ICT resource of smart cities - Hagenauer, F.; Dressler, F.; Altintas, O.; Sommer, Christoph (Smart Cities and Homes)

IEEE 802.11p unicast considered harmful - Klingler, Florian; Dressler, Falko; Sommer, Christoph (2015 IEEE Vehicular Networking Conference (VNC))

Cluster-based transmit power control in heterogeneous vehicular networks - Memedi, Agon; Hagenauer, Florian; Dressler, Falko; Sommer, Christoph (2015 IEEE Vehicular Networking Conference (VNC))

Making cars a main ICT resource in smart cities - Altintas, Onur; Dressler, Falko; Hagenauer, Florian; Matsumoto, Makiko; Sepulcre, Miguel; Sommer, Christoph (2015 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

Timings Matter - Bloessl, Bastian; Puschmann, Andre; Sommer, Christoph; Dressler, Falko (ACM SIGMOBILE Mobile Computing and Communications Review)

Power matters: Automatic Gain Control for a Software Defined Radio IEEE 802.11a/g/p receiver - Bloessl, Bastian; Sommer, Christoph; Dressler, Falko (2015 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

The scrambler attack: A robust physical layer attack on location privacy in vehicular networks - Bloessl, Bastian; Sommer, Christoph; Dressier, Falko; Eckhoff, David (2015 International Conference on Computing, Networking and Communications (ICNC))

Simulative performance evaluation of vehicular networks - Eckhoff, David; Sommer, Christoph (Vehicular Communications and Networks)

Poster: A simulator for heterogeneous vehicular networks - Hagenauer, Florian; Dressler, Falko; Sommer, Christoph (2014 IEEE Vehicular Networking Conference (VNC))

Fairness kills safety: A comparative study for intersection assistance applications - Joerer, Stefan; Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Cigno, Renato Lo; Dressler, Falko (2014 IEEE 25th Annual International Symposium on Personal, Indoor, and Mobile Radio Communication (PIMRC))

Enabling Situation Awareness at Intersections for IVC Congestion Control Mechanisms - Joerer, Stefan; Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Cigno, Renato Lo; Jamalipour, Abbas; Dressler, Falko (IEEE Transactions on Mobile Computing)

MCB – A multi-channel beaconing protocol - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (Ad Hoc Networks)

Towards inter-vehicle communication strategies for platooning support - Segata, Michele; Bloessl, Bastian; Joerer, Stefan; Sommer, Christoph; Gerla, Mario; Cigno, Renato; Dressler, Falko (2014 7th International Workshop on Communication Technologies for Vehicles (Nets4Cars-Fall))

Plexe: A platooning extension for Veins - Segata, Michele; Joerer, Stefan; Bloessl, Bastian; Sommer, Christoph; Dressler, Falko; Cigno, Renate Lo (2014 IEEE Vehicular Networking Conference (VNC))

Toward Communication Strategies for Platooning: Simulative and Experimental Evaluation - Segata, Michele; Bloessl, Bastian; Joerer, Stefan; Sommer, Christoph; Gerla, Mario; Lo Cigno, Renato; Dressler, Falko (IEEE Transactions on Vehicular Technology)

How Shadowing Hurts Vehicular Communications and How Dynamic Beaconing Can Help - Sommer, Christoph; Joerer, Stefan; Segata, Michele; Tonguz, Ozan K.; Cigno, Renato Lo; Dressler, Falko (IEEE Transactions on Mobile Computing)

Information dissemination in vehicular networks - Sommer, Christoph; Dressler, Falko (Vehicular Communications and Networks)

Simulation Tools and Techniques for Vehicular Communications and Applications - Sommer, Christoph; Härri, Jérôme; Hrizi, Fatma; Schünemann, Björn; Dressler, Falko (Vehicular ad hoc Networks)

Adaptive load allocation for combining Anomaly Detectors using controlled skips - Berger, Mario; Erlacher, Felix; Sommer, Christoph; Dressler, Falko (2014 International Conference on Computing, Networking and Communications (ICNC))

Towards an Open Source IEEE 802.11p stack: A full SDR-based transceiver in GNU Radio - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (2013 IEEE Vehicular Networking Conference)

Timings matter - Bloessl, Bastian; Puschmann, Andre; Sommer, Christoph; Dressler, Falko (Proceedings of the 9th ACM international workshop on Wireless network testbeds, experimental evaluation and characterization - WiNTECH '14)

Towards a vehicular cloud - using parked vehicles as a temporary network and storage infrastructure - Dressler, Falko; Handle, Philipp; Sommer, Christoph (Proceedings of the 2014 ACM international workshop on Wireless and mobile technologies for smart cities - WiMobCity '14)

Towards a simulation framework for paraglider networks - Eckert, Juergen; Sommer, Christoph; Eckhoff, David (Proceedings of the 11th ACM symposium on Performance evaluation of wireless ad hoc, sensor, & ubiquitous networks - PE-WASUN '14)

SmartRevoc: An efficient and privacy preserving revocation system using parked vehicles - Eckhoff, David; Dressler, Falko; Sommer, Christoph (38th Annual IEEE Conference on Local Computer Networks)

Driving for Big Data? Privacy Concerns in Vehicular Networking - Eckhoff, David; Sommer, Christoph (IEEE Security & Privacy)

On the impact of street width on 5.9 GHz radio signal propagation in vehicular networks - Erlacher, Felix; Klingler, Florian; Sommer, Christoph; Dressler, Falko (2014 11th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

The Role of Parked Cars in Content Downloading for Vehicular Networks - Malandrino, Francesco; Casetti, Claudio; Chiasserini, Carla-Fabiana; Sommer, Christoph; Dressler, Falko (IEEE Transactions on Vehicular Technology)

Short paper: Vehicle shadowing distribution depends on vehicle type: Results of an experimental study - Segata, Michele; Bloessl, Bastian; Joerer, Stefan; Sommer, Christoph; Lo Cigno, Renato; Dressler, Falko (2013 IEEE Vehicular Networking Conference)

Towards energy efficient smart phone applications: Energy models for offloading tasks into the cloud - Segata, Michele; Bloessl, Bastian; Sommer, Christoph; Dressler, Falko (2014 IEEE International Conference on Communications (ICC))

A networking perspective on self-organizing intersection management - Sommer, Christoph; Hagenauer, Florian; Dressler, Falko (2014 IEEE World Forum on Internet of Things (WF-IoT))

A cluster based architecture for intersection collision avoidance using heterogeneous networks - Tung, Lung-Chih; Mena, Jorge; Gerla, Mario; Sommer, Christoph (2013 12th Annual Mediterranean Ad Hoc Networking Workshop (MED-HOC-NET))

Decoding IEEE 802.11a/g/p OFDM in software using GNU radio - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (Proceedings of the 19th annual international conference on Mobile computing & networking - MobiCom '13)

An IEEE 802.11a/g/p OFDM receiver for GNU radio - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (Proceedings of the second workshop on Software radio implementation forum - SRIF '13)

To crash or not to crash: Estimating its likelihood and potentials of beacon-based IVC systems - Joerer, Stefan; Segata, Michele; Bloessl, Bastian; Cigno, Renato Lo; Sommer, Christoph; Dressler, Falko (2012 IEEE Vehicular Networking Conference (VNC))

A Vehicular Networking Perspective on Estimating Vehicle Collision Probability at Intersections - Joerer, Stefan; Segata, Michele; Bloessl, Bastian; Lo Cigno, Renato; Sommer, Christoph; Dressler, Falko (IEEE Transactions on Vehicular Technology)

Use both lanes: Multi-channel beaconing for message dissemination in vehicular networks - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (2013 10th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

Fair and adaptive data dissemination for Traffic Information Systems - Schwartz, Ramon S.; Ohazulike, Anthony E.; Sommer, Christoph; Scholten, Hans; Dressler, Falko; Havinga, Paul (2012 IEEE Vehicular Networking Conference (VNC))

On the applicability of fair and adaptive data dissemination in traffic information systems - Schwartz, Ramon S.; Ohazulike, Anthony E.; Sommer, Christoph; Scholten, Hans; Dressler, Falko; Havinga, Paul (Ad Hoc Networks)

On the applicability of Two-Ray path loss models for vehicular network simulation - Sommer, Christoph; Joerer, Stefan; Dressler, Falko (2012 IEEE Vehicular Networking Conference (VNC))

How shadowing hurts vehicular communications and how dynamic beaconing can help - Sommer, Christoph; Joerer, Stefan; Segata, Michele; Tonguz, Ozan; Cigno, Renato Lo; Dressler, Falko (2013 Proceedings IEEE INFOCOM)

IVC in Cities: Signal Attenuation by Buildings and How Parked Cars Can Improve the Situation - Sommer, Christoph; Eckhoff, David; Dressler, Falko (IEEE Transactions on Mobile Computing)

Cooperative Awareness at Low Vehicle Densities: How Parked Cars Can Help See through Buildings - Eckhoff, D.; Sommer, Christoph; German, R.; Dressler, F. (2011 IEEE Global Telecommunications Conference - GLOBECOM 2011)

On the Necessity of Accurate IEEE 802.11P Models for IVC Protocol Simulation - Eckhoff, David; Sommer, Christoph; Dressler, Falko (2012 IEEE 75th Vehicular Technology Conference (VTC Spring))

Comparing apples and oranges? - Joerer, Stefan; Dressler, Falko; Sommer, Christoph (Proceedings of the ninth ACM international workshop on Vehicular inter-networking, systems, and applications - VANET '12)

Toward reproducibility and comparability of IVC simulation studies: a literature survey - Joerer, Stefan; Sommer, Christoph; Dressler, Falko (IEEE Communications Magazine)

Content downloading in vehicular networks: Bringing parked cars into the picture - Malandrino, F.; Casetti, C.; Chiasserini, C. F.; Sommer, Christoph; Dressler, F. (2012 IEEE 23rd International Symposium on Personal, Indoor and Mobile Radio Communications - (PIMRC))

Performance Evaluation of Network Mobility Handover over Future Aeronautical Data Link - Ayaz, Serkan; Hoffmann, Felix; Sommer, Christoph; German, Reinhard; Dressler, Falko (2010 IEEE Global Telecommunications Conference GLOBECOM 2010)

Toward Realistic Simulation of Intervehicle Communication - Dressler, Falko; Sommer, Christoph; Eckhoff, David; Tonguz, Ozan (IEEE Vehicular Technology Magazine)

Strong and affordable location privacy in VANETs: Identity diffusion using time-slots and swapping - Eckhoff, David; Sommer, Christoph; Gansen, Tobias; German, Reinhard; Dressler, Falko (2010 IEEE Vehicular Networking Conference)

Simulative performance evaluation of the simTD Self Organizing Traffic Information System - Eckhoff, David; Gansen, Tobias; Manz, Robert; Thum, Daniela; Klages, Oliver; Sommer, Christoph (2011 The 10th IFIP Annual Mediterranean Ad Hoc Networking Workshop)

SlotSwap: strong and affordable location privacy in intelligent transportation systems - Eckhoff, David; German, Reinhard; Sommer, Christoph; Dressler, Falko; Gansen, Tobias (IEEE Communications Magazine)

Adaptive beaconing for delay-sensitive and congestion-aware traffic information systems - Sommer, Christoph; Tonguz, Ozan K.; Dressler, Falko (2010 IEEE Vehicular Networking Conference)

A computationally inexpensive empirical model of IEEE 802.11p radio shadowing in urban environments - Sommer, Christoph; Eckhoff, D; German, R; Dressler, F (2011 Eighth International Conference on Wireless On-Demand Network Systems and Services)

Traffic information systems: efficient message dissemination via adaptive beaconing - Sommer, Christoph; Tonguz, Ozan; Dressler, Falko (IEEE Communications Magazine)

On the Impact of Human Driver Behavior on Intelligent Transportation Systems - Dressler, Falko; Sommer, Christoph (2010 IEEE 71st Vehicular Technology Conference)

Emissions vs. Travel Time: Simulative Evaluation of the Environmental Impact of ITS - Sommer, Christoph; Krul, Robert; German, Reinhard; Dressler, Falko (2010 IEEE 71st Vehicular Technology Conference)

On the feasibility of UMTS-based Traffic Information Systems - Sommer, Christoph; Schmidt, Armin; Chen, Yi; German, Reinhard; Koch, Wolfgang; Dressler, Falko (Ad Hoc Networks)

Improving the Accuracy of IVC Simulation Using Crowd-sourced Geodata - Sommer, Christoph; Eckhoff, David; Dressler, Falko (PIK - Praxis der Informationsverarbeitung und Kommunikation)

Simulation of Ad Hoc Routing Protocols using OMNeT++ - Sommer, Christoph; Dietrich, Isabel; Dressler, Falko (Mobile Networks and Applications)

Simulating the Influence of IVC on Road Traffic using Bidirectionally Coupled Simulators - Sommer, Christoph; Yao, Zheng; German, Reinhard; Dressler, Falko (27th IEEE Conference on Computer Communications (INFOCOM 2008): IEEE Workshop on Mobile Networking for Vehicular Environments (MOVE 2008))
We discuss the need for bidirectional coupling of network simulation and road traffic microsimulation for evaluating Vehicular Ad Hoc Networks (VANETs) in a simulation framework. As the selection of a mobility model influences the outcome of simulations to a great deal, the use of a representative model is necessary for producing meaningful evaluation results. Based on these observations, we present a hybrid simulation framework composed of the road traffic simulator SUMO and the network simulator OMNeT++. The coupled simulation environment is used for an evaluation of two protocols for incident warning in VANETs.

Virtual Cord Protocol (VCP): A flexible DHT-like routing service for sensor networks - Awad, Abdalkarim; Sommer, Christoph; German, Reinhard; Dressler, Falko (2008 5th IEEE International Conference on Mobile Ad Hoc and Sensor Systems)

Requirements and objectives for secure Traffic Information Systems - Dressler, Falko; Sommer, Christoph; Gansen, Tobias; Wischhof, Lars (2008 5th IEEE International Conference on Mobile Ad Hoc and Sensor Systems)

Realistic Simulation of Network Protocols in VANET Scenarios - Sommer, Christoph; Dietrich, Isabel; Dressler, Falko (2007 Mobile Networking for Vehicular Environments)

On the need for bidirectional coupling of road traffic microsimulation and network simulation - Sommer, Christoph; Yao, Zheng; German, Reinhard; Dressler, Falko (Proceeding of the 1st ACM SIGMOBILE workshop on Mobility models - MobilityModels '08)

Progressing toward realistic mobility models in VANET simulations - Sommer, Christoph; Dressler, Falko (IEEE Communications Magazine)

The DYMO Routing Protocol in VANET Scenarios - Sommer, Christoph; Dressler, Falko (2007 IEEE 66th Vehicular Technology Conference)